Gaming the system: how predators induce prey to make themselves more vulnerable - Ydenberg, Ron; Young, Sherry; Sullivan-Lord, Rachel (Frontiers in Ethology, 2023)
There is strong selection for prey animals to avoid capture by predators, which creates selection for predatory tactics that increase capture success. Here we describe a natural situation that appears to match theoretical scenarios in which predators tactically influence the food -safety trade-off faced by prey to increase their vulnerability. By using low-cost 'false attacks' or otherwise advertising their presence, predators force prey to spend time in refuges, in hiding, or in other forms of safety-enhancing behavior during which foraging is impaired or impossible.Prey must compensate by taking extra risks at other times or places to meet their energy requirements, and as a consequence become easier to capture. The natural situation described here involves over-ocean flocking (OOF) by Pacific dunlins (Calidris alpina pacifica). OOF is a safe but energetically expensive alternative to traditional roosting, and largely replaced the latter in Boundary Bay of southwest British Columbia as the presence of wintering peregrines rose during the 1990s. Peregrines appear to use 'false' or 'non-serious' attacks to shift the occurence of OOF to a tidal time frame earlier than is ideal for dunlins, thereby creating later good hunting opportunities. The shift is estimated to increase dunlin mortality substantially. Prominent perching, salient signals and the unpredictable appearances used by many predators could have evolved because this forces prey to increase their level of caution, which may render them more vulnerable at other times or places.